Utilization of data-analytics in the field of procurement - Halonen, Lauri (My University, 2023)
As the importance of procurement as part of companies' daily business grows, so does the need to develop it. The aim of this pro-graduate thesis is to provide a better overview of procurement, data-analytics, and data-analytics in procurement. To achieve this goal, a comprehensive theoretical basis on the concepts of procurement and data-analytics is collected, and the current level of data-analytics utilization in the procurement department of a Finnish manufacturing company is analyzed. The thesis includes a literature review and an empirical study. The literature review utilizes classic works on procurement and data-analytics. The study of data-analytics in procurement draws on the latest research on the topic. The empirical part utilized semi-structured interviews and a multi-part survey. The results of the thesis showed that the role of procurement data-analytics and its use is growing significantly, and the resources devoted to it are highly company and industry dependent. An important factor for the effective use of procurement data-analytics was found to be the creation of a clear data management model and the integration of the data strategy into the business strategy of the company. Enabling resources was also identified as a significant factor for the effective use and development of procurement data-analytics. Overall, procurement data-analytics and its effective use are an important part of the overall development of procurement.

Hankintatoimen merkityksen kasvaessa osana yritysten päivittäistä liiketoimintaa, kasvaa myös sen kehittämisen tarpeellisuus. Tämän pro-gradu tutkielman tavoitteena on luoda parempi kokonaiskuva hankinnasta ja data-analytiikasta. Tavoitteen saavuttamiseksi kerätään kattava teoriapohja hankinnan ja data-analytiikan käsitteistä, sekä analysoidaan suomalaisen valmistavan teollisuuden yrityksen hankintaosaston data-analytiikan hyödyntämisen nykytasoa. Tutkielma pitää sisällään kirjallisuuskatsauksen ja empiirisen tutkimuksen. Kirjallisuuskatsaus hyödyntää hankinnan ja data-analytiikan klassikko teoksia. Hankinnan data-analytiikan tutkimisessa on hyödynnetty uusimpia tutkimuksia aiheesta. Empiria osassa hyödynnettiin puolistrukturoituja haastatteluja ja moni osaista kyselyä. Tutkielman tuloksissa havaittiin, että hankinnan data-analytiikan ja sen hyödyntämisen rooli kasvaa koko ajan merkittävästi ja siihen käytetyt resurssit ovat hyvin yritys- ja toimiala riippuvaisia. Merkittäväksi tekijäksi hankinnan data-analytiikan tehokkaan hyödyntämisen kannalta todettiin selkeän datan hallinta mallin luominen ja datastrategian liittäminen osaksi yrityksen liiketoimintastrategiaa. Myös resurssien mahdollistaminen havaittiin merkittäväksi tekijäksi hankinnan data-analytiikan tehokkaan hyödyntämisen ja kehittämisen kannalta. Kokonaisuudessaan hankinnan data-analytiikka ja sen tehokas hyödyntäminen ovat merkittävässä osassa hankinnan kokonaisvaltaista kehittämistä.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management